URGENSI MANAJEMEN KEUANGAN PADA PENDIDIKAN - Fatonah, Kuni (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2021)
Education is very important for all human beings. Education can be successful if there is good management and good management. The role of educational management is very important in an educational institution. Management is basically not a new thing in human life, as well as in a management education is very necessary. Educational management can cover various things, one of which is in financial management. Because, with good financial management in institutions will increase the efficiency of education so that the achievement of educational goals will soon be realized. The purpose of this research is to collect or analyze articles related to Educational Financial Management. The method used is the review article. The results of this study indicate that financial management in an educational institution has an important role in the advancement of education.